Every Law Has its Loophole?: An Assessment of Political Party Financing - Tuesta Soldevilla, Fernando (2006)
Political party financing is a crucial aspect of politics. This article provides an overview of the Political Parties Law (LPP), enacted in November 2003, and evaluates its application in the Peruvian legal system. The authors aim to objectively analyze the law and its impact. The LPP addresses previously unregulated areas of party life, but also presents deficiencies. The text reflects on the significance of norms in political representation and financing of political parties. It is expected that future regulatory reforms will be transparent and promote democracy by reducing the interference of private interests. A public subsidy is suggested to achieve this goal. Achieving this goal requires the collaboration of an independent supervisory body with the ability to verify the information provided by political parties, as well as an effective system of sanctions to ensure compliance.